Formulation and Antibacterial Activity of Averrhoa bilimbi L. Fruits Extract in Vegetable Oil-Based Liquid Hand Soap - Hayati, Rima; Sari, Amelia; Hanum, Faridah; Nabilah, Nada; Earlia, Nanda; Lukitaningsih, Endang (Malacca Pharmaceutics, 2023)
The main method of preventing infections is good hand cleanliness. Bilimbi (Averrhoa bilimbi) fruits contains flavonoids, which have been tested for antibacterial activity. Polar chemicals like flavonoids are often extracted using ethanol as a solvent.  Therefore, this study aimed to formulate an ethanol extract of A. bilimbi fruits in the form of hand soap. This formulation used vegetable oils such as olive oil, coconut oil, and castor oil, which are high in fatty acids to maintain healthy skin. Antibacterial activity was carried out against Staphylococcus aureus and Escherichia coli. The extract was prepared by maceration for 5 days using an ethanol solvent. Liquid soap contained A. bilimbi fruit extracts at 5% (F1) and 10% (F2). The F1 and F2 organoleptic tests showed the preparation as a thick liquid with a distinctive coconut oil aroma, light brown (F1) and brown (F2) color. pH values of 5.8 (F1) and 5.6 (F2). Foam height stability was 71.5% (F1) and 73.1% (F2). The specific gravity for the two formulas was 1.02 g/mL. The viscosity of F1 and F2 was 137.6 cP and 163.5 cP, respectively. Inhibition power against S. aureus using the agar diffusion method by measuring the diameter of the inhibition zone showed strong (F1) and very strong (F2) categories The inhibition against S. aureus showed strong (F1) and very strong (F2) categories. While F1 has no inhibitory power against E. coli, F2 showed inhibition in the strong category. Based on our research, it can be concluded that A. bilimbi fruit extract can produce good hand soap and have bacteria-inhibiting activity. However, further formula development is still needed to obtain preparations that meet all the requirements and stability tests.